2020
DOI: 10.1158/2159-8290.cd-20-0735
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF Complex Mutations Promote Thyroid Tumor Progression and Insensitivity to Redifferentiation Therapies

Abstract: Mutations of subunits of the SWI/SNF chromatin remodeling complexes occur commonly in cancers of different lineages, including advanced thyroid cancers. Here we show that thyroidspecific loss of Arid1a, Arid2 or Smarcb1 in mouse Braf V600E -mutant tumors promotes disease progression and decreased survival, associated with lesion-specific effects on chromatin accessibility and differentiation. As compared to normal thyrocytes, Braf V600E -mutant mouse PTCs have decreased lineage transcription factor expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 92 publications
5
42
0
Order By: Relevance
“…Our findings confirm other studies suggesting that loss of SMARCA4, SMARCA2 or SMARCB1 expression is more commonly associated with morphologically poorly differentiated tumours 10,39 . It is worth noting that, in cases with only focal loss of expression, the onset of SWI/SNF complex deficiency was associated with morphological dedifferentiation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings confirm other studies suggesting that loss of SMARCA4, SMARCA2 or SMARCB1 expression is more commonly associated with morphologically poorly differentiated tumours 10,39 . It is worth noting that, in cases with only focal loss of expression, the onset of SWI/SNF complex deficiency was associated with morphological dedifferentiation.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Saqcena et al . demonstrated that mutations in SWI/SNF genes result in loss of chromatin accessibility at thyroid lineage genes in BRAF‐mutant thyroid tumours, resulting in insensitivity to the redifferentiation effects of mitogen‐activated protein kinase blockade 39 . This may be in line with our findings in multivariate Cox regression, where any loss of SMARCA4 expression and global loss of SMARCA2 expression cancelled significant effects of BRAF V600E mutation in multivariate analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, mutations in these genes occur in a small fraction of HCC. Mutations in chromatin regulatory proteins were also reported at low frequency, similar to other clinically aggressive thyroid cancers (22,24,32,33). Overall, these studies were consistent with the notion that HCC represented a molecularly distinct form of thyroid cancer.…”
Section: Low Frequency Of Canonical Fdtc Driver Mutationssupporting
confidence: 79%
“…However, the investigations of genotype–phenotype correlations regarding the alterations in FGs in PTCs are very limited. A previous study using mouse thyroid cancer cell lines showed that loss of SWI/SNF subunits was related to radioiodine refractoriness and resistant to MAPK inhibitor-based redifferentiation therapies in BRAF V600E -mutant PTCs, which needs validation in humans [ 17 ]. Mutations in PI3K/AKT/mTOR pathway were reported frequently in advanced thyroid cancers (PDTC or ATC) especially in metastatic or recurrent cases, and also in follicular thyroid carcinomas [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%